2016
DOI: 10.1016/j.toxicon.2016.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of six aspartate (D) recombinant mojastin mutants (r-Moj): A second aspartate amino acid carboxyl to the RGD in r-Moj-D_ peptides is not sufficient to induce apoptosis of SK-Mel-28 cells.

Abstract: Disintegrins are small peptides produced in viper venom that act as integrin antagonists. When bound to integrins, disintegrins induce altered cellular behaviors, such as apoptotic induction. Disintegrins with RGDDL or RGDDM motifs induce apoptosis of normal and cancer cells. We hypothesized that a second aspartate (D) carboxyl to the RGD is sufficient to induce apoptosis. Five recombinant mojastin D mutants were produced by site-directed mutagenesis (r-Moj-DA, r-Moj-DG, r-Moj-DL, r-Moj-DN, and r-Moj-DV). Stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Our research group have demonstrated that substituting one or two of the amino acids immediately carboxyl of the RGD of r-Moj resulted in the elimination of platelet aggregation inhibition for the r-Moj-DM mutant (Table 2), the introduction of apoptotic inducing activity for r-Moj-DM (Ramos et al, 2016) and r-Moj-MP (Fig. 3A), and activity potency differences for mutants produced for the Ramos et al (2016) study and the current one.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Our research group have demonstrated that substituting one or two of the amino acids immediately carboxyl of the RGD of r-Moj resulted in the elimination of platelet aggregation inhibition for the r-Moj-DM mutant (Table 2), the introduction of apoptotic inducing activity for r-Moj-DM (Ramos et al, 2016) and r-Moj-MP (Fig. 3A), and activity potency differences for mutants produced for the Ramos et al (2016) study and the current one.…”
Section: Discussionmentioning
confidence: 94%
“…Expression and purification of r-Moj-WL, r-Moj-WM, r-Moj-WP, r-Moj-WN, r-Moj-MN, r-Moj-MP, and r-Moj-NM peptides were performed with a method described earlier (Ramos et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations